Clinical Presentations of Benign Intraconal Tumors - Memon Muhammad Khan, Partab Rai, Asad Raza Jafri, Muhammad Saeed Iqbal (Pakistan Journal of Ophthalmology, 2008)
Purpose: To determine the clinical presentations of benign intraconal orbital tumors for early diagnosis and prompt treatment. Material and Methods: This study was conducted in the Department of Ophthalmology, Jinnah Post graduate Medical Centre, Karachi from March 2004 to February 2006.Total 30 patients of all age groups with axial proptosis and mass in the intraconal region seen on CT scan or MRI were included and followed for one year. Patients’ presenting complains and clinical examination (ocular/systemic) were noted. Diagnosis of disease was confirmed on the histopathology of excised mass. Results: The commonest clinical presentation was axial proptosis in all (100%) cases followed by decreased visual acuity in 18 (60%) cases, corneal exposure in 5 (16.66%) cases, choroidal folds in 4 (13.33%) cases and complete loss of vision in 3 (10%) cases caused by compression of optic nerve. Histopathology showed Lymphangioma in 11 (36.66%) cases, Cavernous heamangioma in 9 (30%), Neurofibroma in 4 (13.33%), Schwannoma in 3 (10%), Heamangiopericytoma in 2 (6.66%) and Optic nerve glioma in 1 (3.33%) case. Conclusion: Early diagnosis on the basis of clinical presentation, imaging and histopathologically can prevent lose of vision and other complications.